THE LAW OF NASAB FOR CHILDREN BORN OUTSIDE OF LEGAL MARRIAGE ACCORDING TO IMAM IBN QAYYIM AL-JAUZIYYAHحكم نسب الولد في نكاح الحامل من الزنا غير محصن عند الإمام ابن قيم الجوزية - Muhammad Rosyid Ridlo; Imron rosyadi; M Muthoifin (Profetika: Jurnal Studi Islam, 2022)
In this day and age there is a lot of adultery, especially among young people, we often hear news around us or on social media, that a man has committed adultery with a woman who is not his makhram then the woman is pregnant with the man and they both have no marriage relationship with someone else or both were still single, then they both got married to cover their disgrace. It is not uncommon to hear news of a man having an illicit relationship with a woman who is not his wife and even getting pregnant from the illicit relationship while they already have a legal marriage relationship with their respective partners. So there is a polemic among the people about the law of the lineage of the child, can his lineage be attributed to his biological father while he was born outside a legal marriage relationship?